Adjunctive Interventions for Endometriosis: A Review of Current Literature - Węgrzyn, Jagoda; Waśniowska, Magdalena; Wiernek, Magdalena (Journal of Education, Health and Sport, 2025)
Background Endometriosis is a complex disease that affects many women globally. The efficacy of medication is not at its best, despite advancements in therapeutic approaches. The need for further useful, evidence-based solutions grows along with theoretical knowledge. Among these, food, exercise, and psychological support all have a potential therapeutic role when combined with pharmaceuticals. Aim The aim of this article is to assess whether it is appropriate to treat physical activity, food, and psychological therapy as therapeutic interventions in a clinical environment and to investigate their function in treating endometriosis as a supplement to medication. Review methods A comprehensive analysis of research papers available on PubMed and Google Scholar was undertaken using the search terms encompassing the following keywords: endometriosis, endometriosis pain, endometriosis management, endometriosis treatment, diet, dietary intervention, anti-inflammatory diet, supplementation, psychotherapy, psychological intervention, pain management, exercises. Conclusions Non-pharmacological interventions, including physical activity, physiotherapy, dietary modification and psychological therapies, offer valuable complementary benefits. Evidence suggests that structured exercise, pelvic-floor physiotherapy, anti-inflammatory dietary patterns and cognitive-behavioral or mindfulness-based interventions can reduce pain, enhance functional capacity and improve mental health. Cannabinoid therapy shows promise but requires more robust clinical research. Overall, integrating lifestyle, psychological and rehabilitative strategies alongside conventional treatment provides a more holistic and patient-centered approach, addressing the biological, functional and psychosocial dimensions of endometriosis.